FORMING STUDENTS' GRAPHIC COMPETENCES WITH THE HELP OF COMPARATIVE TEACHING AS A PEDAGOGICAL PROBLEM - Raxmonjonov Xusan Akbarovich (Web of Journals Publishing, 2025)
This article considers the issue of using comparative teaching methods in the formation of students graphic competencies as a pedagogical problem. Graphic literacy is an important competency in modern education, and interactive and comparative teaching methods are necessary for its effective development. The article describes the theoretical foundations, practical possibilities of comparative teaching, and proposals for its integration into the educational process.
Keywords: Comparative teaching, graphic competence, pedagogical problem, visual thinking, teaching methods, comparison, analytical thinking.